Pengaruh Kolaborasi Thinking Learning Dan Tekateki Dalam Meningkatkan Kreatifitas Siswa Di SMPIT At Taisiriyah Sukabumi - Fahmi Muhamad Aziz; Kun Nurachadijat (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The implementation of the 2013 curriculum learning which is now being held in several schools, emphasizes the learning process based on the development of students' cognitive activities that are creative and productive. Puskurbuk (retnawati, 2016) argues that the 2013 curriculum is required to be able to produce productive, creative, innovative and affective human resources, through strengthening attitudes, knowledge, and skills competencies. Think creatively so innovations and ideas will emerge including using puzzles, puzzles are a method that is very enjoyable and is able to make class consistency in learning creative, innovative and fun, the puzzle method is also very stable when combined between thinking learning and puzzles which hopefully can become a good collaboration and effect in a lesson. The purpose of this research is to find out the collaboration of thinking learning and puzzles in increasing the creativity of students at the smpit at taisiriyah sukabumi after using this method. This research method is a qualitative research conducted on October 23, 2022 to October 26, 2022. The place of this research is at the taisiriyah school of Sukabumi. The object of research is class VIII at smpit at taisiriyah Sukabumi. The results of the collaborative thinking learning and puzzles themselves can increase student learning creativity, this can be seen from the achievement of very high indicators of creativity. For students who have advantages or tend to learn more easily by means of audio less portion because this learning character focuses more on pictures or illustrations. The material is appropriate for learning other general subjects. Conclusion Collaborative thinking learning and puzzles can help students better understand various concepts, improve memory, and simply make learning more interesting. It is very beneficial to apply mind mapping to various fields of teaching and study